Implementation of Curriculum Development Based on KTSP Principles at SD Negeri Cibiru 06 Cileunyi Bandung City - Haris, Nurfadhilah; Ali, Rifki Zulfikar; Erihadiana, Mohamad (AS-SABIQUN, 2023)
This type of research is qualitative research using inductive data analysis because this research seeks to determine curriculum development at SD Negeri Cibiru 06 Cileunyi. The method used in collecting data is observation, interviews, and documentation. The main roles in the development of the KTSP are the principal, teachers, and school committee. Curriculum development involves the government, universities, curriculum experts, and various walks of life. The results of this study are goal orientation, relevance, efficiency, flexibility, continuity, balance, integration, and quality. In the implementation of the curriculum at SD Negeri Cibiru 06 Cileunyi the following principles are applied: 1) Implementation of the curriculum is based on the potential, development, and condition of students to acquire competencies that are beneficial to students. 2). The curriculum is implemented by adhering to the five pillars of learning. 3) Implementation of the curriculum allows students to use the service. 4). The curriculum is delivered in an atmosphere of student-educator relations that provides power and strength, builds enthusiasm and initiative, and provides examples and role models going forward. 5). The curriculum is implemented using a multi-strategic and multimedia approach, learning resources, and technology. 6) The curriculum is carried out with optimal content of all learning materials, utilizing natural, social and cultural conditions as well as local wealth for educational success. 7) The curriculum which contains all elements of professional competence, local content, and self development is carried out with a balance, linkage, and continuity that is reasonable and appropriate between classes and levels of education